Estudo antropométrico, clínico e de padrões alimentares em um grupo de escolares de Manaus, 1976 - Giugliano, Rodolfo; Albuquerque, Helyde C. R.; Shrimpton, Roger (Acta Amazonica, 1978)
A group of 69 children in the first year of a State School in a poor area of urban Manaus, Amazonas, was subjected to clinical, anthropometric and dietary studies. Eighty-five percent of the children were malnourished when compared by height and/or weight to the Harvard Growth Pattern. Clinical evidence of anaemia and Vitamin A deficiencies were high. The frequency of end of the first year exam failure was higher in malnourished children. The food pattern seemed good from a qualitatively point of view but referred to Sunday. The school children were regular beneficiaries of the National School Snack Campaign (CNAE).